Resilience in health workers: The role of social support and calling - Koamesah, Grace Tesabela; Virlia, Stefani; Musa, Muwaga (Psikohumaniora: Jurnal Penelitian Psikologi, 2022)
Health workers are professionals with high exposure to various types of stress; therefore, they need resilience to survive in their profession. This research aims to test the effect of social support and calling on resilience in health workers.  It is a quantitative-correlational study conducted cross-sectionally. The instruments used were the Connor-Davidson Resilience Scale, Multidimensional Support Scale, and Calling Scale. Snowball sampling was used to identify participants, consisting of 113 health workers in East Nusa Tenggara province, Indonesia. The data were analyzed with multiple linear regression techniques. Significant effects of social support and calling were found on resilience (p < .01, F = 34.224), with calling shown to have more significant impact (p < .01, F = 60.685) and 35.3% effective contribution. Amongst the types of social support, coworkers make the most significant contribution of 11.8% (p < .01, F = 14.816), followed by family members at 9.6% (p < .01, F = 11.752). On the other hand, social support from supervisors does not affect resilience (p > .05, F = 0.904). Health workers should seek the social support they need proactively, and prospective health workers should consider their calling when choosing a career.